Developing a Strategic Marketing Plan for Academic Library E-resources to Optimize Return on Investment. Issue 3 (2nd October 2017) - Nagra, Kanu A.
Abstract: Developing and executing a marketing plan to increase the awareness and utilization of community and academic library e-resources depends upon awareness of internal factors such as budget, staffing, time, and collaboration within library units. More importantly, external factors such as how users find resources, collaboration with academic departments, and how using available communication venues to disseminate messages about resources, play a role. This paper reviews the literature on the purpose and reasons for developing a marketing plan and provides a model based on the author's experience showing how to produce a strategic marketing plan to maximize the library's return on investment (ROI).